A practical numerical approach to solve a fractional Lotka–Volterra population model with non-singular and singular kernels. (April 2021) - Ravi Kanth, A.S.V.; Devi, Sangeeta
Abstract: This paper investigate the dynamical behavior of the fractional Lotka–Volterra dynamic model. The proposed model is examined through fractional derivatives with singular and non-singular kernels. The Newton polynomial-based computational scheme is used to solve the Lotka–Volterrapopulation model with non-local operators. An error estimation of the proposed method is given. The findings of the simulation reveal that the model provided on the basis of three separate fractional operators displays distinct asymptomatic actions that do not exist within the modeling of the integer-order. Finally, computational results are presented to check the accuracy of the scheme, we compared the results with the existing methods.